Capability on paying back microfinance loan: a case study in Bank Simpanan Nasional (HQ) Jalan Ampang Kuala Lumpur / Nordiyana Ayuni Zakaria - Zakaria, Nordiyana Ayuni (Faculty of Business and Management, 2010)
The main problem faced nowadays in banking and financial institutions, especially those who provide loans like personal loans, micro loans, and business loans is how to maintain their margin while to keep the borrowers to pay back on time. The main problem faced by these institutions, example in the case of Bank Simpanan Nasional (BSN), is how to find the solutions so that the payment will be on time and no default account can exist. However, not all the solutions implemented will bring the result their wanted. The aim of this research is to analyze the condition of the scenario. It is also needed to find the factors or reasons behind the failure to pay by interpreting the scenario of the borrowers and also from the side of bank itself. From that, the space between it can be filled, as the solutions can be studied and more ways can be done to help the solutions to work. To work on this research, a case study is done with a framework of unstructured interview is done to gain more inside information about this topic. Other than that, field trip to borrowers’ house also helps to listen and understand their reason of failure to pay. The solutions to make the borrowers pay on time has its good impact, however not all are precise in returning the results. The bank needs to sharpen their actions from the early stages of production; the need to eliminate unqualified applicant, so that cases such as default account can be eliminate and also through all the process in the production itself.